Rancang Bangun Game Pengenalan Tokoh Cerita Rakyat Berbasis Android Menggunakan Model Incremental - Putra, Moch Andria Reza Effendi; Nugroho, Hendro; Rachman, Andy (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2024)
The advancement of information technology in multimedia, computer hardware, and software has increased the needs of society, especially in games. Although folklore plays a central role in shaping culture, people's knowledge of folklore has declined, especially among students. This research offers a solution through the development of a game as a learning tool to reintroduce folklore stories and characters to kids. The research method involved literature observation, collecting information on characters in folklore, and interviews to gather data for designing the game. Application development employed the incremental model with the steps of requirement, design, coding, testing, and implementation. Evaluation through a post-test aims to assess students' abilities related to folklore after application development. The game application development was carried out using the Unity Game Engine. The evaluation yielded 77% for understandability, 74% for learnability, 77% for operability, 81% for attractiveness, and 79% for usability compliance. The total average score for usability factors reached 78%.